Beliefs in conspiracy theories about COVID-19 vaccines in the Andean Community of Nations (2022)
Studies on the acceptance and rejection of vaccines, as well as the belief in conspiracy theories, and the lack of trust in governments and science, have been important to analyze the vaccination process against COVID-19 worldwide, but they have been quite limited, so far, in the case of Latin America. In this sense, the objective of this work is to describe the degree of acceptance or not of certain conspiracy beliefs about vaccines against COVID-19 in a sample of countries members in the Andean Community of Nations (CAN): Bolivia, Colombia, Ecuador and Peru. A descriptive cross-sectional study was designed in which 1835 people from Bolivia, Colombia, Ecuador and Peru participated. To evaluate these beliefs, the COVID-19 Vaccine Conspiracy Belief Scale (ECCV-COVID, Caycho-Rodríguez et al., 2022a) was used. The results indicate that Peru has the highest average score of conspiracy beliefs about vaccines against COVID-19. In addition, in the 4 countries, the lowest degree of acceptance is with the belief that "Vaccinating children against COVID-19 is harmful and this fact is hidden". In Colombia, Ecuador and Peru, the highest degree of acceptance is related to the conspiratorial belief that "Information on the safety of vaccines against COVID-19 is often invented." Finally, in Bolivia, the highest degree of acceptance is with the belief that "Pharmaceutical companies hide the dangers of vaccines against COVID-19". The results presented in this study are the first known generically in the Latin American population, and particularly in the Andean population. © 2022 Instituto de Altos Estudios de Salud Publica. All rights reserved.